Effect of Public Expenditures on the Performance of Bayelsa State Economy, Nigeria - Mathias Avendei (WORLD JOURNAL OF FINANCE AND INVESTMENT RESEARCH, 2026)
Public expenditure plays a significant role in promoting economic growth, infrastructural development, employment generation, and poverty reduction in developing economies. This study examines the effect of public expenditures on the performance of the Bayelsa State economy between 2014 and 2025. The study adopts an ex-post facto research design using secondary data obtained from Bayelsa State budget reports, Central Bank of Nigeria publications, National Bureau of Statistics reports, and other government publications. Descriptive statistics, correlation analysis, and multiple regression analysis were employed to examine the relationship between public expenditure and economic performance indicators in Bayelsa State. Findings reveal that capital expenditure has a positive and significant effect on economic growth, infrastructural development, and employment generation, while recurrent expenditure demonstrates mixed outcomes due to rising administrative costs and governance inefficiencies. The study also identifies corruption, weak budget implementation, overdependence on federal allocation, and poor fiscal discipline as major constraints to effective public expenditure management in Bayelsa State. The study concludes that productive and properly managed public expenditures significantly enhance economic performance in Bayelsa State. The study recommends increased capital investment, improved fiscal transparency, stronger public financial management systems, and diversification of the state economy.